Breastfeeding related knowledge, attitudes, perceptions and practices of primary healthcare professionals in Ireland: A national cross-sectional survey - Denise McGuinness; Kate Frazer; Sarah Brennan; Nancy Bhardwaj; Paula Cornally; Siobhan Ni Mhurchu; Marie Cantwell; Anne Pardy; Laura McHugh; Walter Cullen; Niamh Vickers (PLoS ONE, 2025)
Background Global research identifies the importance of breastfeeding, including the World Health Organisation in developing recommendations and noting over 800,000 child lives would be saved each year if breastfeeding was adopted following the recommendations of WHO/UNICEF. There is limited published data exploring breastfeeding knowledge, attitudes, perceptions and practices [KAPP] of health care professionals employed in primary care. Recent Irish evidence from one local geographical area identified general practitioners and general practice nurses [GPs and GPNs] received limited formal breastfeeding education within undergraduate or postgraduate education programmes and were interested in undertaking further professional development, education and training. Methods Following ethical approval, a national cross sectional online survey using a breastfeeding [KAPP] survey instrument was completed using the Qualtrics platform. All registered GPs, GP trainees and General Practice Nurses [GPNs] in the Republic of Ireland were invited to participate. The online survey link was distributed via Ireland’s Health Service Executive health link email register via two senior HSE gatekeepers. Data collection was from June 1st 2023, to November 17th, 2023. Results A total of 662 primary health professionals participated, including 58.2% GPs, 14.2% GP trainees and 27.6% GPNs. The response rate to the survey was 10%, with approximately 6618 healthcare professionals receiving the link to the survey and 662 participating. Approximately 78% of respondents reported always recommending breastfeeding to women, and the majority (94.2%) were interested in completing further breastfeeding education. Barriers to training noted were time (84.3%), workload (62%) and financial cost (34.9%). Perceived and factual breastfeeding knowledge, perceived attitude and confidence scores with breastfeeding related issues significantly differed among the three groups. Conclusion This national study reports low engagement with a national KAPP survey. There is inadequate preparation of primary healthcare professionals both theoretically and clinically to promote, protect and support breastfeeding in the primary healthcare setting, and has important implications for supporting wellbeing and shaping population health and achieving sustainable development goals.